On the Stability of Quadratic Functional Equations in F-Spaces. (25th July 2016) - Yang, Xiuzhong
Abstract : The Hyers-Ulam-Rassias stability of quadratic functional equation f ( 2 x + y ) + f ( 2 x - y ) = f ( x + y ) + f ( x - y ) + 6 f ( x ) and orthogonal stability of the Pexiderized quadratic functional equation f ( x + y ) + f ( x - y ) = 2 g ( x ) + 2 h ( y ) in F -spaces are proved.